Samidorphan mitigates olanzapine-induced weight gain and metabolic dysfunction in rats and non-human primates - Jacobi I Cunningham; David J Eyerman; Mark S Todtenkopf; Reginald L Dean; Daniel R Deaver; Connie Sanchez; Mark Namchuk (Figshare, 2019)
Background:
Olanzapine, regarded as one of the most efficacious antipsychotic medications for the treatment of schizophrenia, is associated with a high risk of weight gain and metabolic dysfunction. ALKS 3831, a clinical candidate for treatment of schizophrenia, is a combination of olanzapine and samidorphan, an opioid receptor antagonist. The addition of samidorphan is intended to mitigate weight gain and the metabolic dysregulation associated with the use of olanzapine.
Methods:
Non-clinical studies were conducted to assess the metabolic effects of olanzapine and samidorphan alone and in combination at clinically relevant exposure levels.
Results:
Chronic olanzapine administration in male and female rats shifted body composition by increasing adipose mass, which was accompanied by an increase in the rate of weight gain in female rats. Co-administration of samidorphan normalized body composition in both sexes and attenuated weight gain in female rats. In hyperinsulinemic euglycemic clamp experiments conducted prior to measurable changes in weight and/or body composition, olanzapine decreased hepatic insulin sensitivity and glucose uptake in muscle while increasing uptake in adipose tissue. Samidorphan appeared to normalize glucose utilization in both tissues, but did not restore hepatic insulin sensitivity. In subsequent studies, samidorphan normalized olanzapine-induced decreases in whole-body glucose clearance following bolus insulin administration. Results from experiments in female monkeys paralleled the effects in rats.
Conclusions:
Olanzapine administration increased weight gain and adiposity, both of which were attenuated by samidorphan. Furthermore, the combination of olanzapine and samidorphan prevented olanzapine-induced insulin insensitivity. Collectively, these data indicate that samidorphan mitigates several metabolic abnormalities associated with olanzapine in both the presence and the absence of weight gain.
Keywords: 110904 Neurology and Neuromuscular Diseases; 111599 Pharmacology and Pharmaceutical Sciences not elsewhere classified; 170199 Psychology not elsewhere classified; 110319 Psychiatry (incl. Psychotherapy); 111599 Pharmacology and Pharmaceutical Sciences not elsewhere classified